Allocytoplasmic restorers and performance of hybrids in rice (Oryza sativa L.) - K. Rukmini Devi*, K. Rajendra Prasad and P. Jaganmohan Rao (Electronic Journal of Plant Breeding, 2021)
Combining ability analysis for yield and quality traits of 54 rice hybrids developed by crossing three CMS lines and eighteen restorers in L x T design were evaluated in RBD. The magnitude of additive genetic variance (ϭ2A) was higher than dominance variance for days to 50% flowering, effective tillers, kernel length after cooking and volume expansion ratio indicating the predominance of additive gene action. However, for the rest of the characters non additive gene action was predominant. The relative contribution of testers were high for days to 50% flowering(79.6%), self fertility (72.8%) and flag leaf length (79.9%), indicating influence of parents and interaction contribution (L x T) was high for filled seeds/panicle, yield/plant (57.0%) and hulling percent (63.5%). Among the lines 68897A showed significant gca effects in the desirable direction and identified as best combiner for yield/plant, days to 50% flowering, effective tillers, panicle density, hulling percent, head rice recovery, kernel width after cooking, water uptake and volume expansion ratio, while 79156A for self fertility, filled seeds/panicle and panicle length. Among the male parents RR15 was found to be good combiner for panicle length, filled seeds/panicle, unfilled seeds/panicle, self fertility, test weight, yield/plant and RR 23 for effective tillers, panicle length and head rice recovery. The cross combinations 68897 A x RR 23, 68897 A x RR 32, 68897 A x RR55 and 79156 A x RR3 recorded significant sca effects for yield/plant and were relatively better performed for desired yield and quality traits based on sca effects, per se performance and gca effects of parents.